AN ENERGY FUNCTION APPROACH FOR FINDING ROOTS OF CHARACTERISTIC EQUATION - Deepak Mishra; Prem K. Kalra (ICTACT Journal on Soft Computing, 2011)
In this paper, an energy function approach for finding roots of a characteristic equation has been proposed. Finding the roots of a characteristics equation is considered as an optimization problem. We demonstrated that this problem can be solved with the application of feedback type neural network. The proposed approach is fast and robust against variation of parameter.